OPTIMASI PRODUKSI SENYAWA AKTIF HASIL FERMENTASI MIKROBA SIMBION SPON BYT 7 - , Annisa Fitria; , Dr. rer. nat., Yosi Bayu Murti, M.Si., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Sponge associated microorganism have a high potential to produce bioactive compounds. Increased production of secondary metabolites is a success key of microbes utilization for the production of active compounds. This research was conducted to determine the optimum condition for the microbial fermentation. Variables of fermentation applied on this experimental study were: agitation conditions (0 rpm, 60 rpm, 150 rpm), the additions of carbon (dextrose: 1%, 5%,10%), nitrogen (yeast extract: 2.5%, 7.5%,12.5%), and salinity (5â°, 15â°, 35 â°) of fermentation media. Three parameters that have been analyzed for each fermentation variables, were : growth curve profile, MIC of the extract and amount of its active compound. Liquid culture samples were taken and measured every 24 hours during a week by turbidity methode to determine microbial symbiont growth curve. Each extract was tested for its antimicrobial activity by the microdilution technique against Staphylococcus aureus. Quantitative analysis of active compounds was determined by TLC-Densitometry. Result of this study showed a relationship among three parameters that have been analyzed with the fermentation variables. Production of active compound could increased by using the optimal medium composition as follows: concentration of 1% dextrose, 12,5% yeast extract concentration and salinity of 35 â° and agitation speed of 150 rpm.